Blood biomarkers for new-onset hypertension in midlife women: a nested case-control study. Issue 2 (20th February 2023) - He, Zhen; Yang, Peixuan; Lin, Qiuqiang; Thio, Chris H.L.; Zhang, Fan; Wang, Ruifeng; Wang, Yue; Snieder, Harold; Zhang, Qingying
Abstract : In addition to obesity and metabolic dysregulation, the findings of this study indicate that higher hemoglobin, counts of platelets, red blood cells, and white blood cells are associated with higher risk of hypertension in midlife women. Knowledge on the effects of these variables on hypertension will contribute to defining more specific strategies for prevention and treatment of hypertension in this population. Abstract: Objective: Midlife in women is associated with an increase in prevalence of hypertension. Little is known on the risk factors of new-onset hypertension among middle-aged women. Methods: In this nested case-control study, 1, 430 women aged 40 to 60 years with repeated physical examinations between 2009 and 2019 were recruited. Data included age, body mass index, blood pressure (BP), and a series of blood biomarkers. Participants with hypertension were divided into two case-control samples: 388 cases with episodic new-onset hypertension (ie, one normal BP at the first visit and one abnormal BP during follow-up) each with two age-matched controls (n = 776) and 151 cases with regular new-onset hypertension (ie, normal BP at the first two visits and abnormal BP at two or more follow-up visits) each with three age-matched controls (n = 453). Multivariable-adjusted logistic regression was used to analyze the data. Results: Our data showed very consistent results for episodic and regular new-onset hypertension, respectively, and verified known associations (odds ratio [95% confidence interval], per SD increase) with obesity (body mass index, 1.72 [1.49-1.98] and 1.81 [1.45-2.26]), inflammation (white blood cell count, 1.39 [1.23-1.58] and 1.38 [1.13-1.69]), and metabolic dysregulation (triglycerides, 1.25 [1.09-1.44] and 1.31 [1.08-1.58]; glucose, 1.46 [1.23-1.73] and 1.27 [1.05-1.54]) but, more surprisingly, also revealed positive associations with red blood cell count (1.27 [1.11-1.44] and 1.38 [1.14-1.68]), hemoglobin (1.18 [1.03-1.35] and 1.31 [1.05-1.64]), and platelet count (1.39 [1.20-1.61] and 1.33 [1.09-1.63]). Conclusions: In addition to obesity and metabolic dysregulation, increased hemoglobin and counts of platelets, and red and white blood cells are associated with hypertension in this period. Future study may verify whether these associations are causal in nature and whether these variables are useful in risk stratification.